2014
DOI: 10.1371/journal.pone.0092753
|View full text |Cite|
|
Sign up to set email alerts
|

High-Lard and High-Fish-Oil Diets Differ in Their Effects on Function and Dynamic Behaviour of Rat Hepatic Mitochondria

Abstract: BackgroundMitochondria are dynamic organelles that frequently undergo fission and fusion processes, and imbalances in these processes may be involved in obesity and insulin resistance.AimsThe present work had the following aims: (a) to evaluate whether the mitochondrial dysfunction present in the hepatic steatosis induced by a high-fat diet is associated with changes in mitochondrial dynamics and morphology; (b) to evaluate whether effects on the above parameters differ between high-lard and high-fish-oil diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
129
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(156 citation statements)
references
References 60 publications
23
129
2
2
Order By: Relevance
“…Fis1 is a protein participating in the mitochondrial fission process. Over-expression of Fis1 induced by excess nutrients has been reported in many studies [13,47,48]. As expected, catalpol can inhibit Fis1 expression in HFD/STZ-diabetic mouse livers (Fig.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Fis1 is a protein participating in the mitochondrial fission process. Over-expression of Fis1 induced by excess nutrients has been reported in many studies [13,47,48]. As expected, catalpol can inhibit Fis1 expression in HFD/STZ-diabetic mouse livers (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, a reduction in mitochondrial fusion was considered to be a key risk factor in the development of obesity and insulin resistance [45]. Enhanced fission machinery has also been found in the liver of genetically obese and diet-induced obese animals [12,13]. In order to figure out the regulation mechanism of catalpol on hepatocyte mitochondrial ATP content, the expressions of genes related to these events were analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there is a mitochondrial network function that depends on signaling molecules and the relationship between mitochondrial fusion and fission. While mitochondrial fission is orchestrated by the dynamin-related protein 1 (DRP1) and the mitochondrial fission 1 (Fis1) protein [34], [35], the fusion process is controlled by the autosomal dominant optic atrophy 1 (OPA1) protein, together with the mitochondrial fusion proteins mitofusion 1 and 2 (Mfn 1 and 2), located on the mitochondrial outer membrane, [36], [37]. As HO-1/HO-2 are known regulators of mitochondrial integrity and function [38], [39], [40], [41], we hypothesized that adipose HO-1 gene is essential for increased mitochondrial fusion that may result in an increase in the beige cell population within adipose tissue or conversion of white adipose function populations and white adipose function that include expression of PGC1α levels and thermogenic genes.…”
Section: Introductionmentioning
confidence: 99%
“…Under-reporting is an important bias in epidemiological studies on diet and obesity in human subjects; therefore animal models have been widely utilized for experiments on dietary obesity [10]. Lionetti et al reported that lard (40% fat J/J) aggravated liver injury as indicated by increased hepatic TNF-a and infiltration of inflammatory cells compared with fish oil (40% fat J/J) in a 6 week feeding study in rats [11]. In contrast, as for the effect of high-fat diet (HFD) on the lungs in the absence of any acute injury, lard-based HFD (60 kcal% fat) did not influence inflammatory cytokines in the lung tissue after 3 weeks feeding [12], or in BALF after 9 weeks feeding [13] in mice.…”
Section: Introductionmentioning
confidence: 99%